Locations of Religious Encounter: The Scandinavian Diaspora in the Viking Age - Abrams, Lesley (Studies in church history, 2025)
This article examines the process of conversion to Christianity of Scandinavians who left their homelands in the ninth and tenth centuries and settled in Christian societies in the West. The churches that were involved left us no accounts, but fragments of evidence ranging from papal letters to stone sculpture help to construct a picture of diversity, wherever routes to conversion can be glimpsed across this Scandinavian diaspora. Two contrasting settings - Normandy, soon after the Viking Rollo was put in charge in 911, and northern England, under the authority of Scandinavian kings from the late ninth to the mid-tenth century - are discussed, highlighting the agency of churchmen at the interface between paganism and Christianity. The sources hint at contrasting dynamics and a range of strategies, from creativity to coercion, as churches faced the challenge of bringing immigrant Scandinavians into the Christian centre.